Observing Ramadan and sleep-wake patterns in athletes: a systematic review, meta-analysis and meta-regression - Trabelsi, K.; Bragazzi, N.; Zlitni, S.; Khacharem, A.; Boukhris, O.; El-Abed, K.; Ammar, A.; Khanfir, S.; Shephard, R. J.; Hakim, A.; Moalla, W.; Chtourou, H. (British Journal of Sports Medicine, 2020)
Objective: To evaluate the effect of observing Ramadan on athletes` sleep patterns.